(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article examines real estate investments as a key sector that ensures economic growth and serves as a stable source of income. Improving investment accounting in this field is essential not only for enhancing financial performance but also for managing risks and making strategic decisions. This paper explores the main methods and approaches necessary for improving the accounting of real estate investments.